The Effect of Quality of Work Life, Work Motivation and Job Satisfaction on Employee Performance at Hypermart Bengkulu - Aldha Pebriana Aziz; Merta Kusuma (Jurnal Ekonomi, Manajemen, Akuntansi dan Keuangan, 2024)
This research aims to determine the influence of Quality of Work Life, Work Motivation and Job Satisfaction on Employee Performance at Hypermart Bengkulu. The population in this study was Hypermart Bengkulu employees, totaling 50 people. The sampling technique in this research is to use total sampling where the entire population is sampled, namely 50 employees. Data collection methods use observation and questionnaires. The data analysis technique used is multiple linear regression, coefficient of determination and hypothesis. Based on the research results, it can be seen that the Quality of Work Life variable has a significant effect on employee performance at Hypermart Bengkulu, seen from the significant value of 0.000, which is smaller than 0.05. Then work motivation has an influence because the significant value of 0.028 is smaller than 0.05. And job satisfaction also has an influence because the significance value of 0.000 is smaller than 0.05. The coefficient of determination R square is 0.461. This means that the performance of Hypermart Bengkulu employees can be explained by 46.1% by independent variables, namely the influence of quality of work life, work motivation and job satisfaction. Meanwhile, the remainder (100-46.1% = 53.9%) was influenced by other causal factors not examined in this study.